FRI0142 SAFETY OF THE METHOTREXATE-LEFLUNOMIDE COMBINATION IN THE BRAZILIAN REGISTRY OF BIOLOGICAL THERAPIES IN RHEUMATIC DISEASES (BIOBADABRASIL). (June 2019) - Bredemeier, Markus; Pinheiro, M; Macieira, C; Duarte, A; Stadler, B; Ranza, R; Medeiros, Ana; Valim, V; Bertolo, M; Miranda, J; Brenol, C; Castro, G; et al.
Abstract : Background: The combination of methotrexate (MTX) with leflunomide (LEF), despite being effective in the therapy of rheumatoid arthritis (RA)[1], has not been widely accepted[2, 3]. In spite of evidence that the MTX-LEF combination is generally safe [1, 4, 5], the relatively small number of patients and treatment courses have not permitted firm conclusions. Objectives: To evaluate the safety of the combination MTX-LEF in Brazilian patients with RA included in BiobadaBrasil. Methods: BiobadaBrasil is a multicentric prospective cohort study involving patients with rheumatic diseases who started the first biologic or a synthetic disease modifying anti-rheumatic drug (DMARD)[6]. This analysis includes RA (2010 criteria) patients recruited from Jan 2009 to Aug 2018, followed-up for one or multiple courses of treatment until censoring (latest date, September 03, 2018) or occurrence of the outcome of interest. The primary outcome was the incidence of any serious AE (SAE). Secondary outcomes were infectious, non-mycobacterial pulmonary infectious, hepatic, hematologic and cardiovascular SAE. Multivariate Cox proportional hazards models (with DMARDs included as time-varying covariates) were used to estimate hazard ratios (HR) and 95% confidence intervals (CI); analyses were performed with the Survival package of R. Results: Sample: 2055 RA patients, female=85.1%, median disease duration=6.02 yrs; mean (SD) age=50.3 (12.1) yrs; mean (SD) DAS28=5.3 (3.1); seronegative RA=14.1%; median follow-up duration=3.9 yrs. In total, 565 patients received 664 courses of the MTX-LEF combination (median duration, 2.5 years/course; 2209 person-years). The incidence of SAE was 4.75/100 patient-years in the entire sample. There was no significant increase in the risk of any of the outcomes with the use of combined therapy (table 1 ) comparing with methotrexate (without leflunomide). The use of antimalarials was associated with reduced risk of SAE (adjusted HR=0.62, 95% CI 0.48 to 0.79, P<0.001), while sulfasalazine (adj. HR= 1.78, 1.18 to 2.68, P=0.006) and biologic DMARDs/tofacitinib (adj. HR= 1.67, 1.31 to 2.12, P<0.001) increased the risk of SAE. Conclusion: BIOBADABRASIL results suggest that the combination of methotrexate and leflunomide is safe in thetreatment of RA. References: [1] Ann Intern Med 2002; 137: 726. [2] Ann Rheum Dis 2010; 69: 43. [3] Ann Pharma cother 2004; 38: 1206. [4] J Rheumatol 2013; 40: 228. [5] Rev Bras Reumatol 2011; 51: 141/51:152. Acknowledgement: monitor P Cabral Disclosure of Interests: Markus Bredemeier: None declared, M Pinheiro Consultant for: Janssen, Pfizer, Speakers bureau: Abbot, Janssen, Novartis, C Macieira: None declared, A Duarte: None declared, B Stadler: None declared, R Ranza: None declared, Ana Medeiros: None declared, V Valim: None declared, M Bertolo: None declared, J Miranda Speakers bureau: Pfizer, C Brenol Speakers bureau: Pfizer, Roche, Janssen, Bristol., G Castro: None declared, V Fernandes Speakers bureau: Janssen, D Titton: None declared, F Sauma: None declared, I Pereira: None declared, R Botelho: None declared, H Carvalho: None declared, A Hayata: None declared, P Louzada: None declared, A Ranzolin: None declared, I Silveira: None declared, S Schowalski: None declared, D Feldman: None declared, I Laurindo Consultant for: Abbvie, UCB, GSK, JANSSEN, LILLY, NOVARTIS, PFIZER, Paid instructor for: Abbvie, JANSSEN, Speakers bureau: Abbvie, UCB, GSK, JANSSEN, LILLY, NOVARTIS, PFIZER, ROCHE, J Provenza: None declared